Helicopter Mothers and Helicopter Fathers: Italian Adaptation and Validation of the Helicopter Parenting Instrument - Pistella, Jessica; Izzo, Flavia; Isolani, Stefano; Ioverno, Salvatore; Baiocco, Roberto (Psychology Hub, 2020)
The aim of this study is to validate the Italian version of the Helicopter Parenting Instrument (HPI), a self-report instrument that evaluate adolescents’ and young adults’ perception of parenting behaviors. The term helicopter parenting describes a style of child-rearing characterized by parents who are over-involved in every aspect of their children’s lives in inappropriate ways, compromising their autonomy. The HPI (maternal and paternal version) was administered to 602 adolescents (356 females), between 14 and 18 years of age (Mfemales = 16.56; SD = 1.43; Mmales = 16.63; SD = 1.41). The factorial analysis confirmed the original one-factor structure for both versions. The two versions of the instrument demonstrated good concurrent and divergent validity and the reliability was high. In general, our participants perceived mothers with higher levels of helicopter parenting than fathers, regardless of gender and age of the participants. In conclusion, the instrument demonstrated good psychometric properties, indicating that it may be a valid measure for evaluating parental overparenting in the Italian context.